A Case Study Combining Online Social Media and Video to Teach News Literacy. (September 2014) - Spikes, Michael A.; Haque, Yousuf S.
With the rise of information availability and the speed at which it can be disseminated, it is now the consumer's job to exercise more discernment and to become more skeptical about the information coming across their screens. This is a major point in the argument to adopt a relatively new academic discipline known as News Literacy. A subset of media literacy, News Literacy focuses solely on the consumption of news items—whether it is a blurb from a friend, a blog, or a reputable news source. The News Literacy course seeks to equip news consumers with a set of tools to help them determine the reliability of incoming information. This allows them to access the news before they perpetuate it to their own social networks. To test the efficacy of certain aspects of the News Literacy course, such as verification of information disseminated through social networks, the researchers developed an interactive learning activity to enable students to experience the process via a fictionalized story. This article will explain the reasoning behind the activity's development and will also report the results of the first case study executed in a News Literacy class at Stony Brook University in the spring of 2014.